Two Types of Argument from Position to Know - Botting, David (Informal Logic)

(untitled) (Informal Logic, 2018)
In this paper I will argue that there is an inductive and a non-inductive argument from position to know, and will characterise the latter as an argument from (epistemic) authority because of providing content-independent reasons. I will also argue that both types of argument should be doubt-preserving: testimony cannot justify a stronger cognitive attitude in the arguer than the expert herself expresses when she testifies. Failure to appreciate this point undercuts Mizrahi’s (2013) claim that arguments from expert opinion are weak.